2005
DOI: 10.1002/jlcr.947
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis of carbon‐11‐labelled GI181771, a new selective CCK‐A agonist

Abstract: SummaryThe novel CCK-A agonist, (S)-3-(3-f1-[(isopropylphenylcarbamoyl)methyl]-2,4-dioxo-5-phenyl-2,3,4,5-tetrahydro-1H-benzo [b][1,4]diazepin-3-ylgureido)benzoic acid, GI181771 ((S)-1) has been isotopically labelled with carbon-11 at its urea site using [ 11 C]phosgene in a one-pot two-step process, via the intermediate preparation of an specific radioactivities ranging from 500 to 1500 mCi/mmol (18.5-55.5 GBq/mmol). The radiotracer preparation was a clear and colourless solution and its pH was between 5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Following heating, the contents of the vial were transferred to a quench vial containing water (0.3 mL). Argon was bubbled through the resultant mixture in order to transfer any unreacted 11 CO into the waste bag. The vial was then removed from the hot cell; its radioactivity was measured, and a 20-μL aliquot was removed for HPLC analysis.…”
Section: Preparation Of Cutp* Trapping Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following heating, the contents of the vial were transferred to a quench vial containing water (0.3 mL). Argon was bubbled through the resultant mixture in order to transfer any unreacted 11 CO into the waste bag. The vial was then removed from the hot cell; its radioactivity was measured, and a 20-μL aliquot was removed for HPLC analysis.…”
Section: Preparation Of Cutp* Trapping Solutionmentioning
confidence: 99%
“…Urea functional groups are an obvious target for [ 11 C]CO radiolabelling as this group is found in many biologically relevant molecules. Traditionally, [ 11 C]ureas have been prepared using [ 11 C]phosgene, a reagent that is notoriously difficult to prepare in a reliable manner and is used at only a few PET facilities worldwide. Alternatively, [ 11 C]ureas have been synthesized from [ 11 C]CO at high pressures using selenium or rhodium catalysts; however, these approaches are restricted to the formation of cyclic or symmetrical species (with selenium) or require the synthesis of an azide precursor (with rhodium).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects observed during fasting suggested that the CCK1R mechanisms may be pharmacologically targeted to alter fasting gastric function. With the aim of using this agonist as a radioligand for molecular and functional imaging studies by positron emission tomography (PET), 32a has been labeled with the positron emitter isotope 11 C at the ureido group carbon [63]. Additionally, to further explore the binding sites of 1,5-benzodiazepine-derived agonists and antagonists at the CCK1 receptor, the two resolved enantiomeric pairs of benzophenone derivatives 32b,c and 32d,e, previously reported as racemic agonists and antagonists, respectively [64], have been recently prepared labeled with 14 C also at the ureido group, to be used as radioligands and photoaffinity probes [65].…”
Section: 5-benzodiazepine Derivativesmentioning
confidence: 99%
“…[ 11 C]Benazoline was obtained in 16% overall yield, relative to [ 11 C]CO 2 and with a specific radioactivity of 54 GBq/mmol., decay corrected from end of irradiation. In order to get a better understanding of this system, investigations for the radiolabelling feasibility of GI181771, CCK-A agonist, with carbon-11 were realized [271]. In order to get a better understanding of this system, investigations for the radiolabelling feasibility of GI181771, CCK-A agonist, with carbon-11 were realized [271].…”
Section: [ 11 C]rcooh As Acylating Agentmentioning
confidence: 99%